Dental Anomalies in Children with Cleft Lip and Palate at a Tertiary Care Hospital - Qurat-ul-Ain, Faiza Malik, Sumaira Anwar Khan, Hamna Khawaja, Ayesha Sadaf, Mustafa Qadeer (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To determine the dental anomalies in children with cleft lip and palate at a tertiary care hospital. Design of the Study: descriptive cross-sectional. Study Settings: Study was conducted at conducted in the OPD of Dentistry at Abbottabad International Medical Institute between the months of January 2021to June 2021. Material and Methods: The convenience sampling strategy was used to obtain the 208 radiographs of patients with cleft lip and/or palate for Data A. In order to conduct the study, the Institutional Review Board granted its approval. Radiographs were examined for suspected dental defects and demographic information was gathered. Results of the Study: A total of 76 (38 in group A and B) patients were included. Mean age in groups A and B was 39.25±3.91 and 38.71±4.01. Out of 38 patients in group A and B, effectiveness of large antecubital vein versus small vein on dorsum of hand in prevention of propofol injection was 81.6% vs. 36.87%. Conclusion: A high rate of dental abnormalities has been found in patients who have had a cleft lip or palate. The most common aberration in the study was tooth agenesis, with the lateral incisor having the highest rate of agenesis.